Atomic Habits : an easy & proven way to build good habits & break bad ones: tiny changes - "Clear, James" (London; Cornerstone Press, 2022)
"People think when you want to change your life, you need to think big. But world-renowned habits expert James Clear has discovered another way. He knows that real change comes from the compound effect of hundreds of small decisions - doing two push-ups a day, waking up five minutes early, or holding a single short phone call. He calls them atomic habits. In this ground-breaking book, Clears reveals exactly how these minuscule changes can grow into such life-altering outcomes. He uncovers a handful of simple life hacks (the forgotten art of Habit Stacking, the unexpected power of the Two Minute Rule, or the trick to entering the Goldilocks Zone), and delves into cutting-edge psychology and neuroscience to explain why they matter. Along the way, he tells inspiring stories of Olympic gold medalists, leading CEOs, and distinguished scientists who have used the science of tiny habits to stay productive, motivated, and happy."-- Back cover
Keywords: Behavior modification